Prostate angiogenesis in development and inflammation. Issue 4 (30th November 2013) - Wong, Letitia; Gipp, Jerry; Carr, Jason; Loftus, Christopher J.; Benck, Molly; Lee, Sanghee; Mehta, Vatsal; Vezina, Chad M.; Bushman, Wade
Abstract BACKGROUND Prostatic inflammation is an important factor in development and progression of BPH/LUTS. This study was performed to characterize the normal development and vascular anatomy of the mouse prostate and then examine, for the first time, the effects of prostatic inflammation on the prostate vasculature. METHODS Adult mice were perfused with India ink to visualize the prostatic vascular anatomy. Immunostaining was performed on the E16.5 UGS and the P5, P20, and adult prostate to characterize vascular development. Uropathogenic E. coli 1677 was instilled transurethrally into adult male mice to induce prostate inflammation. RT‐PCR and BrdU labeling was performed to assay anigogenic factor expression and endothelial proliferation, respectively. RESULTS An artery on the ventral surface of the bladder trifurcates near the bladder neck to supply the prostate lobes and seminal vesicle. Development of the prostatic vascular system is associated with endothelial proliferation and robust expression of pro‐angiogenic factors Pecam1, Tie1, Tek, Angpt1, Angpt2, Fgf2, Vegfa, Vegfc, and Figf. Bacterial‐induced prostatic inflammation induced endothelial cell proliferation and increased vascular density but surprisingly decreased pro‐angiogenic factor expression. CONCLUSIONS The striking decrease in pro‐angiogenic factor mRNA expression associated with endothelial proliferation and increased vascular density during inflammation suggests that endothelial response to injury is not a recapitulation of normal development and may be initiated and regulated by different regulatory mechanisms. Prostate 74:346–358, 2014. © 2013 Wiley Periodicals, Inc.